Two-color laser modulation of magnetic Feshbach resonances - 李健 刘勇 黄寅 丛书林 (Chinese physics B, 2015)
We investigate the two-color laser modulation of the magnetically induced Feshbach resonance. The two-color laser is nearly resonant with an optical bound-to-bound transition at the resonance position. The analytical formula of scattering length is obtained by solving the Heisenberg equation. The scattering length can be modified by changing the Rabi frequencies or optical field frequency. By choosing the suitable optical parameters, the two-body loss coefficient K2 can be greatly reduced compared to the usual single optical scheme.